Efficiency gains from micro-irrigation: a case of sprinkler irrigation in wheat - Prabhat Kishore (Agricultural Economics Research Review, 2023)
This paper assesses the efficiency gains from the adoption of sprinkler irrigation using data from a farm survey in the water-scarce, drought-prone Bundelkhand region of Uttar Pradesh. Our analysis goes beyond the conventional comparison of physical and economic parameters between micro-irrigation with flood irrigation. We estimate gains in crop yield, water productivity, and technical efficiency, correcting for omitted variable bias. Our findings show that sprinkler irrigation significantly improves yield (21%), water productivity (34%), and technical efficiency (20%); in other words, it saves water (15%) and diesel (8%). These findings are confirmed by our econometric estimates.